Risk Resilience of International Production Cooperation among BRICS Countries - L. V. Zubova (Евразийская интеграция: экономика, право, политика, 2025)
Aim and tasks. This study is devoted to the development of a methodology for assessing the risk resilience of international production cooperation (IPC) among BRICS countries. It covers the introduction of conceptual and categorical apparatus, practical testing of the assessment method, identification of key problems in military-economic cooperation among BRICS countries, and modeling of risks that affect the level of IPC’s risk resilience. These risks are grouped into clusters to develop strategies for enhancing resilience. Methods. The foundation and methods of the research include a systems approach, SWOT analysis, statistical, comparative, and cluster analyses, as well as expert evaluations. Results and conclusions. The key features of military-economic cooperation among BRICS countries have been identified, along with the proposed conceptual and categorical apparatus and a method for assessing the level of IPC risk resilience. The author proposes establishing risk resilience management centers for IPC in BRICS countries. These centers would be responsible for forecasting, monitoring, evaluating, and managing the risk resilience of IPC participants, identifying areas of responsibility and results achieved in management. Additionally, scientific research should be conducted at these centers on integrating Russian reporting forms with international financial reporting standards into a unified “platform”, refined to a perfect level that allows risks to be reflected both across all accounts and business transactions within a single methodology. Only through such integration will accounting procedures be simplified in cross-country interactions, data will become transparent and easily understandable in accounting, leaving managers free to focus solely on genuine managerial activities without distractions.